Three Dimensions for SCO to Improve Legislation (Халықаралық қатынастар және халықаралық құқық сериясы, 2024)
The 21st century is the “era of international organizations”. the SCO is facing a realistic dilemma of “insufficient rule orientation”, “imperfect international law system” and “uneven level of rule of law among its members”. International law has its own structural dilemma of uncertainty, which lies in structure, language and doctrine, and overturns the existing international law system. Within the framework of the SCO, the traditional normal way can’t quickly and effectively establish legislation. The argumentative paradigm is rooted in the “intersubjectivity” of the international community, reshaping the effectiveness and source scope of international law, and using this paradigm can quickly and effectively build a set of international law system for SCO. This paradigm needs value guidance in line with universal rationality. The “community with a shared future for mankind” proposed by the Chairman Xi Jinping is expected to achieve the multi-dimensional goals of common prosperity, universal security, openness and win-win results, equality and inclusiveness, and joint construction, which can provide a value orientation for the development of SCO international law. This paper focuses on the SCO, tries to elaborate the problems faced by the SCO from the perspective of international law, and puts forward the research paradigm of improving the construction of SCO international law and the value orientation of “community with a shared future for mankind” on the basis of its system, in order to further clarify the direction of efforts to build the SCO legal system. Under the guidance of the theory of community with a shared future for mankind, the SCO’s practice of argumentative international law can improve the legal system construction within the organization on the basis of maintaining regional peace, and then contribute to the SCO’s participation in world governance and the promotion of the rise of Asia.Keywords: norms, indeterminacy, argumentalism, community with a shared future, SCO